Risk of opportunistic infections in patients treated with alemtuzumab for multiple sclerosis. Issue 7 (3rd July 2018) - Buonomo, Antonio Riccardo; Zappulo, Emanuela; Viceconte, Giulio; Scotto, Riccardo; Borgia, Guglielmo; Gentile, Ivan
ABSTRACT: Introduction : Alemtuzumab is a monoclonal anti CD-52 antibody recently approved for use in relapsing-remitting multiple sclerosis(MS). Given that the targeted antigen is primarily expressed on B and T lymphocytes, the administration of this biological drug is associated with rapid but protracted peripheral lymphopenia. Areas covered : The impact on infective risk of this immune impairment is still to be fully understood. In this review, we attempt to summarize all the available literature concerning opportunistic infections occurring in patients with MS receiving alemtuzumab. Infective adverse events were observed in more than 70% of patients in phase 2/3 RCTs, mainly of mild-to-moderate severity. Nevertheless, several post-marketing reports documented cases of serious, rare, and unexpected infections. Expert Opinion : Predictive risk factors and prognostic features of opportunistic infections in this setting still need to be exactly assessed. At present, the only recommended preventive measures consist in anti-herpetic prophylaxis, Listeria-free diet, Tuberculosis prophylaxis and annual Papillomavirus screening. Given the non-negligible risk of unpredicted infective events, we advise physicians to take into account patients' history of infectious diseases and vaccine status and to consider supplementary prophylactic strategies, including screening for Toxoplasma gondii and viral hepatitis serostatus as well as pre-emptive approaches to avert CMV reactivation and Pneumocystosis.